A importância da energia eólica na matriz energética brasileira: a sustentabilidade como valor instrumental para a diminuição das desigualdades regionais e a efetivação do direito ao desenvolvimento no Ceará - Gondim, Liliane Sonsol (2013)
The fundamental right to development integrates a national project that has its basis settled in the constitution text, whose guidelines impose social transformations. Therefore, it has an instrumental feature in overcoming regional inequalities and improving the quality of human life. Considering the insertion of the Brazilian energy matrix in that project and its importance for development, it is necessary to discuss the issues relating to the national energy development model, in the state of Ceará’s perspective. The discussion is guided by legal and social values constitutionally bound: the environment and the reduction of regional inequalities. This perspective requires recognition of the transformative power of the Constitution, primarily through public policies, which are not always used for this purpose and can often deviate from the constitutional objectives. Along the way, most desirable options in the social and environmental points of view, such as wind power, are deprecated in favor of polluting and expensive options. When faced with the institutional arrangement of the national power sector and the problems stemming from its poor planning and public policy dissociated from constitutional objectives, it is clear that this orientation produces undesirable economic, social and environmental effects and calls for a new development standard based on social, economical and environmental sustainability.